Severity Assessment in CDKL5 Deficiency Disorder - Demarest, Scott (Pediatr Neurol, 2019)
BACKGROUND: Pathological mutations in cyclin-dependent kinase-like 5 cause CDKL5 deficiency disorder (CDD), a genetic syndrome associated with severe epilepsy, cognitive, motor, visual and autonomic disturbances. CDD is a relatively common genetic cause of early-life epilepsy. A specific severity assessment is lacking, required to monitor clinical course, define the natural history and for clinical trial readiness. METHODS: A severity assessment was developed based on clinical and research experience from the International Foundation for CDKL5 Research Centers of Excellence consortium and the NIH Rett and Rett-related disorders Natural History Study consortium. An initial draft severity assessment was presented and reviewed at the annual CDKL5 Forum meeting (Boston, 2017). Subsequently it was iterated through four cycles of a modified Delphi process by a group of clinicians, researchers, industry, patient advisory groups and parents familiar with this disorder until consensus was achieved. The revised version of the severity assessment was presented for review, comment and piloting to families at the International Foundation for CDKL5 Research sponsored family meeting (Colorado, 2018). Final revisions were based on this additional input. RESULTS: The final severity assessment comprised 51 items that comprehensively describe domains of epilepsy, motor, cognition, behavior, vision, speech and autonomic function. Parental ratings of therapy effectiveness, child and family functioning are also included. CONCLUSIONS: A severity assessment was rapidly developed with input from multiple stake-holders. Refinement through ongoing validation is required for future clinical trials. The consensus methods employed for the development of the severity assessment may be applicable to similar rare disorders.